The composition of the choice set modulates probability weighting in risky decisions. - Grubb, M. A.; Li, Y.; Larisch, R.; Hartmann, J.; Gottlieb, J.; Levy, I. (Cognitive, Affective & Behavioral Neuroscience, 2023)
Probability distortion—the tendency to underweight larger probabilities and overweight smaller ones—is a robust empirical phenomenon and an important driver of suboptimal choices. We reveal a novel contextual effect on probability distortion that depends on the composition of the choice set. Probability distortion was larger in a magnitude-diverse choice set (in which participants encountered more unique magnitudes than probabilities) but declined, resulting in more veridical weighting, in a probability-diverse choice set (more unique probabilities than magnitudes). This effect was consistent in two, large, independent datasets (N = 481, N = 100) and held for a subset of lotteries that were identical in the two contexts. It also developed gradually as a function of exposure to the choice set, was independent of attentional biases to probability versus magnitude information, and was specific to probability weighting, leaving risk attitudes unaffected. The results highlight the importance of context when processing probabilistic information.